Modeling of growth during detoxification of coffee residues by filamentous fungi - Hernández-Teyssier, Eva Luz; Anducho-Reyes, Miguel Angel; Díaz-Godínez, Gerardo; Tellez-Jurado, Alejandro (Ecosistemas y Recursos Agropecuarios, 2023)
The modeling of the growth and detoxification of a mixture of coffee residues (MCR) by solid-state fermentation (SSF) from the quantification of metabolic CO2 as an indirect method, growth stoichiometry solution, and monitoring of polyphenols is described. The SSF was carried out in Raimbault columns with Lentinus strigosus, Trichoderma harzianum and two strains of Aspergillus sp.; one isolated from barley straw (Aspergillus sp. ABS) and another from coffee residues (Aspergillus sp. ACR); the CO2 was trapped in a 1.0 M NaOH solution. The solution of the equation gave the conversion factor 3.53 g of CO2 per gram of biomass, and by the modified Gompertz equation, the modeling of biomass with R2 values greater than 0.95; μmax were 0.12 ± 0.01 h−1 for L. strigosus, 0.20 ± 0.03 h−1 for T. harzianum, 0.21 ± 0.01 h−1 for Aspergillus sp. ABS and 0.42 ± 0.08 h−1 for Aspergillus sp. ACR, however, RMSE values, indicate predictions with considered errors. Finally, detoxification was possible in 75.74 ± 6.07% with L. strigosus at 10 days, 56.13 ± 6.92%, and 50.34 ± 4.82% with T. harzianum and Aspergillus sp. ABS, respectively, at 4 days and 32.89 ± 3.17% with Aspergillus sp. ACR at 10 days. The biomass quantification and modeling strategy provides a new tool for the study of SSF, in addition, detoxification is described as consumption of polyphenols as a substrate.
Keywords: Gompertz equation; indirect method; Lentinus strigosus; polyphenols; Trichoderma harzianum